From Womb to World: Immunological Pathways Influencing Stunting and 2030 Sustainability - Yuliastri, Nunuk (RSF Conference Series: Business, Management and Social Sciences, 2024)
Stunting affects 150 million children globally, indicating an existing inequality in nutrition and health; despite focusing on nutrient deficiencies, the immunological continuum from prenatal to postnatal needs to be better described. This study synthesized the literature analyzing the role of immune functions in stunting from prenatal to early childhood and its implications for the 2030 Sustainable Development Goals. The database search was performed on PubMed, Scopus, Web of Science, and Google Scholar, in accordance with the PRISMA 2020 guidelines. The objective of the current narrative review was to determine immunological factors and stunting using peer-reviewed English research published from 2000 to 2024. The review also reveals that stunting is a complex process involving immune and nutritional factors, but the significant determinants of growth are prenatal immune priming and early-life infection. Some findings are related to the knowledge of the interrelation between nutritional deficiencies and immune system dysfunctions, cytokine patterns, and gut microbiota dynamics. Thus, this study provides a general definition of stunting and recommends additional research in immunology and the need for public health measures involving nutritional and immunological interventions. The assessment provides recommendations for preventing stunting and ensures that the actions are aligned with the 2030 Sustainable Development Goals for improving children’s well-being.